Ultrasound-guided platelet-rich plasma vs. radiofrequency nerve ablation for refractory plantar fasciitis - Erdoğan, Furkan; Cengiz, Tolgahan; Yurtbay, Alparslan; Büyükceran, İsmail (The European Research Journal, 2024)
Objectives: Plantar fasciitis (PF), which accounts for approximately 80% of heel pain, is a common condition affecting adults’ quality of life. There are many different treatment modalities used in the treatment of PF. In this study, we compared the clinical and functional outcomes of patients diagnosed with chronic PF in our clinic who underwent USG-guided PRP (platelet-rich plasma) injection and patients who underwent RFNA (radiofrequency nerve ablation) treatment. Methods: Ultrasound-guided PRP injection or RFNA was performed on 95 patients who were diagnosed with chronic PF and met the inclusion criteria. This group of patients was followed for at least one year (October 2021-October 2023), and the clinical and functional results of the patients were compared. Results: The mean pre-treatment Visual Analog Scale (VAS), Foot Function Index (FFI), and American Orthopaedic Foot and Ankle Society (AOFAS) posterior-ankle scores were similar, and no significant difference was found (P>0.05). A significant improvement was observed in the groups’ FFI, VAS, and AFOAS scores after treatment (P<0.05). However, no significant difference was found in treatment modalities (P>0.05). Conclusions: As a result of the study, it was concluded that PRP injection and RFNA are effective treatment methods in patients diagnosed with chronic plantar fasciitis without response to other conservative treatment methods, but these two methods are not superior to each other.